2004
DOI: 10.2337/diacare.27.2.629
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Increases Adiponectin Levels and Insulin Sensitivity in Humans

Abstract: Characteristics of patients with type 2 diabetes in Mexico: results from a large populationbased nationwide survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
136
4
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(160 citation statements)
references
References 8 publications
16
136
4
4
Order By: Relevance
“…Kriketos et al (2004) reported a significant increase in adiponectin levels in obese sedentary males following a short-term exercise training program (approximately 1 week). On the contrary, Ferguson et al (2004) reported no effect of a submaximal aerobic exercise bout on adiponectin concentration in young healthy normal weight individuals.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Kriketos et al (2004) reported a significant increase in adiponectin levels in obese sedentary males following a short-term exercise training program (approximately 1 week). On the contrary, Ferguson et al (2004) reported no effect of a submaximal aerobic exercise bout on adiponectin concentration in young healthy normal weight individuals.…”
Section: Discussionmentioning
confidence: 98%
“…There are studies which have reported no effect of acute exercise on adiponectin levels in healthy, normal weight individuals (Ferguson et al 2004;Kraemer et al 2003;Punyadeera et al 2005). On the other hand, Jurimae et al (2005) reported a significant decrease immediately following exercise and significant increase 30 min post-exercise in healthy normal weight individuals, whereas Kriketos et al (2004) reported that very short exercise training (approximately 1 week) resulted in increased levels of adiponectin and insulin sensitivity in obese individuals without a concomitant body weight loss. It is worth mentioning, that none of the acute studies have examined the probable prolonged effect of exercise on adiponectin levels and its relationship with insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…We observed no consistent association between physical activity and adiponectin, although paradoxically levels were significantly reduced in the vigorously active group. Although it has been suggested that exercise may increase adiponectin levels, clinical studies on the effects of exercise training have been conflicting 41,42 and findings in population-based studies are inconsistent. 19,21 Insulin resistance and the metabolic syndrome Strong associations were seen between adiponectin and HOMA-IR after adjustment for waist circumference and the magnitude of correlation was similar to that seen for BMI.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that basal adiponectin concentration was not altered after longterm exercise [10][11][12][13][14]. In contrast, Kriketos et al [15] recently reported that fasting adiponectin levels increased by 260% above baseline values after 2-3 bouts of low to moderate intensity exercise. Although Hara et al [13] performed a study on young obese men, no reports have been available on adiponectin concentra-tions in obese young women during prolonged and moderate intensity exercise.…”
mentioning
confidence: 96%
“…Several studies exploring the effects of exercise on circulating adiponectin levels have resulted in inconsistent findings [10][11][12][13][14][15]. It has been shown that basal adiponectin concentration was not altered after longterm exercise [10][11][12][13][14].…”
mentioning
confidence: 99%